Test Research on Cooling Performance of Heat-pipe Air-cooling Device for High-speed EMUs Main Converter - LUO Ai-hua; JIN Ying; YUE Liang; JIN Su-min (机车电传动)
Operation principle of high-speed EMUs main converter cooling device was introduced. Heat-transfer character of heat-pipe air-cooling device was studied, and heat dissipating capacity and base-plate temperature range of IGBT cooling device in normal operation were obtained, which provided basis for radiator selection and design.